Aplikasi Pembelajaran Tajwid dan Nagham Al-Qur’an Berbasis Web - Yus Jayusman; Rifqi Fauzi Mubarok; Herna Gunawan (Jurnal Penelitian dan Pengembangan Teknologi Informasi dan Komunikasi, 2024)
Mastery of Tajweed and Nagham Al-Quran is crucial for accurate and melodious Quranic recitation. However, access to qualified teachers or reputable learning institutions is not always readily available to everyone. To address this challenge, this research aims to develop a web-based application that facilitates independent and interactive learning of Tajweed and Nagham Al-Quran. The study employs a structured software development methodology following the Waterfall model. Data collection involved literature reviews and interviews with subject matter experts on Tajweed rules, which served as the foundational basis for developing the application’s content. Key features of the application include modules for learning Tajweed and Nagham, Quranic reading exercises, a Tajweed glossary explaining key terminologies, and audio-visual resources to demonstrate clear examples of recitation.Testing results confirm that the application effectively aids users in comprehending and applying Tajweed and Nagham principles. Functional testing verified that all features operate as intended, highlighting the application’s reliability as a self-directed learning tool. This research concludes that the web-based Tajweed and Nagham Al-Quran learning application provides users with a more accessible and flexible platform to enhance their Quranic recitation skills. Future development is recommended to include a mobile version of the application to improve accessibility. Additional interactive features, such as discussion forums for experience sharing and advanced automated recitation evaluation tools, are also proposed to enhance the learning experience. The application leverages web-based technology and adheres to the Waterfall model to ensure a systematic development process. Its web-based nature enables compatibility across a variety of internet-connected devices, significantly broadening user reach. In summary, this research demonstrates that a Tajweed and Nagham Al-Quran learning application bridges the gap in access to quality education, offering an innovative and effective solution for individuals seeking to deepen their Quranic knowledge and recitation skills.